Understanding the Phase Reversals of Galactic Cosmic-Ray Anisotropies - Bing-Qiang Qiao; Qing Luo; Qiang Yuan; Yi-Qing Guo (The Astrophysical Journal, 2022)
Energy spectra and anisotropies are very important probes of the origin of cosmic rays. Recent measurements show that complicated but very interesting structures exist at similar energies in both the spectra and energy-dependent anisotropies, indicating a common origin of these structures. A particularly interesting phenomenon is that there is a reversal of the phase of the dipole anisotropies, which challenges theoretical modeling. In this work, for the first time, we identify that there might be an additional phase reversal at ∼100 GeV energies of the dipole anisotropies as indicated by a few underground muon detectors and the first direct measurement by the Fermi satellite, coincident with the hundreds of GV hardening of the spectra. We propose that these two phase reversals, together with the energy evolution of the amplitudes and spectra, can be naturally explained with a nearby source overlapping onto the diffuse background. As a consequence, the spectra and anisotropies can be understood as the scalar and vector components of this model, and the two reversals of the phases characterize just the competition of the cosmic-ray streamings between the nearby source and the background. The alignment of the cosmic-ray streamings along the local large-scale magnetic field may play an important but subdominant role in regulating the cosmic-ray propagation. More precise measurements of the anisotropy evolution at both low energies by space detectors and high energies by air shower experiments for individual species will be essential to further test this scenario.